The Distinct Function and Localization of METTL3/METTL14 and METTL16 Enzymes in Cardiomyocytes - Arcidiacono, Orazio Angelo; Krejčí, Jana; Bártová, Eva (International journal of molecular sciences, 2020)
It has become evident that epitranscriptome events, mediated by specific enzymes, regulate gene expression and, subsequently, cell differentiation processes. We show that methyltransferase-like proteins METTL3/METTL14 and N6-adenosine methylation (m6A) in RNAs are homogeneously distributed in embryonic hearts, and histone deacetylase (HDAC) inhibitors valproic acid and Trichostatin A (TSA) up-regulate METTL3/METTL14 proteins. The levels of METTL3 in mouse adult hearts, isolated from male and female animals, were lower in the aorta and pulmonary trunks when compared with atria, but METT14 was up-regulated in the aorta and pulmonary trunk, in comparison with ventriculi. Aging caused METTL3 down-regulation in aorta and atria in male animals. Western blot analysis in differentiated mouse embryonic stem cells (mESCs), containing 10-30 percent of cardiomyocytes, showed METTL3/METTL14 down-regulation, while the differentiation-induced increased level of METTL16 was observed in both wild type (wt) and HDAC1 depleted (dn) cells. In parallel, experimental differentiation in especially HDAC1 wild type cells was accompanied by depletion of m6A in RNA. Immunofluorescence analysis of individual cells revealed the highest density of METTL3/METTL14 in α-actinin positive cardiomyocytes when compared with the other cells in the culture undergoing differentiation. In both wt and HDAC1 dn cells, the amount of METTL16 was also up-regulated in cardiomyocytes when compared to co-cultivated cells. Together, we showed that distinct anatomical regions of the mouse adult hearts are characterized by different levels of METTL3 and METTL14 proteins, which are changed during aging. Experimental cell differentiation was also accompanied by changes in METTL-like proteins and m6A in RNA; in particular, levels and distribution patterns of METTL3/METTL14 proteins were different from the same parameters studied in the case of the METTL16 protein.
Keywords: adenosin; Male; Aging; methyltransferasy; HEK293 buňky; myší embryonální kmenové buňky; Mouse Embryonic Stem Cells; buněčná diferenciace; HEK293 Cells; mužské pohlaví; HeLa buňky; kardiomyocyty; Animals; lidé; ženské pohlaví; HeLa Cells; Humans; zvířata; Methyltransferases; myši inbrední C57BL; stárnutí; Myocytes, Cardiac; myši; Mice, Inbred C57BL; Adenosine; Female; Mice; Cell Differentiation